Belonging to a majority reduces the immediate need threat from ostracism in individuals with a high need to belong. (15th August 2017) - Eck, Jennifer; Schoel, Christiane; Greifeneder, Rainer
Abstract: Ostracism—being ignored and excluded—threatens the basic human needs for belonging, self‐esteem, control, and meaningful existence. This work introduces belonging to a majority as a buffer against the immediate negative impact of ostracism on basic needs for individuals with a high need to belong, for whom social groups are especially relevant. Three studies show that for individuals high in the need to belong, need threat was attenuated by membership in a majority group, but not by membership in a minority group (Studies 1 and 3) or a group of unknown size (Study 2). By contrast, individuals low in the need to belong—who place less importance on group membership in general—did not benefit from belonging to a majority group. The general pattern replicated across different manipulations of group membership and social exclusion, with two measures of need threat, and with participants from two different countries.